A novel way of hook wire placement for surgical resection of suspicious breast lesions using the stereotactic vacuum assisted breast biopsy table. Issue 4 (22nd January 2021) - Michalopoulos, Nikolaos V.; Mitrousias, Apostolos; Karathanasis, Panagiotis V.; Kalles, Vasileios; Frountzas, Maximos; Theodoropoulos, Charalampos; Alafaki, Maria; Zografos, Constantine G.; Chronas, Angelos; Matiatou, Maria; Zografos, George C.
Abstract: Preoperative hook localization is a necessary procedure for targeting impalpable breast lesions. The aim of the current study is to introduce an alternative technique of wire placement by using the stereotactic biopsy device instead of the conventionally used mammography device. Fifty‐one patients with impalpable mammographic lesions, graded BIRADS 4 or 5, were prospectively enrolled. Mean duration was 7 ± 1.5 minutes. Lesion‐to‐wire distance was <1 cm in 96% (51/53). Hook wire placement using the stereotactic biopsy device is considered as a safe, accurate, fast, and well‐tolerable for the patient procedure.